PENGARUH UPA````H MI````NI````````````````````MUM DAN INVESTASI TERHADAP KESEMPATAN KERJA DAN KONSUMSI DI KABUPATEN/KOTA PROVINSI BAL``I - Ida Bagus Putu Purbadharmaja, I Putu Eka Wibawa, (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
This study aims to analyze district minimum wages and investments in employment opportunities in districts /cities in Bali Province, analyze the effect of the number of district minimum wages, investment and employment opportunities on household consumption in the Regency / City of Bali Province, analyze the indirect effect of minimum wages district and investment in household consumption through employment opportunities in the Regency / City of Bali Province. This research was conducted in Bali Province. The data used in this study are time series data from 2013-2017 and cross section data as many as nine regencies / cities in Bali Province. The data analysis technique used in this study is the path analysis technique testing the direct influence and testing of indirect effects using the sobel test. Based on the results of the analysis, the number of district minimum wages has a positive but not significant effect, while investment has a positive and significant effect on employment opportunities. The amount of district minimum wages, investments and employment opportunities has a positive and significant effect on household consumption. Job opportunities do not partially mediate the influence of district minimum wages, while employment opportunities partially mediate the effect of investment on consumption.